Effect of different housing systems (cages versus floor) on energy efficiency analysis of meat type Japanese quails - GOKDOGAN, OSMAN; AYASAN, TUGAY; INCI, HAKAN; SOGUT, BUNYAMIN; SENGUL, TURGAY (The Indian Journal of Animal Sciences, 2016)
The aim of the present study was to make an energy efficiency analysis of Japanese quails reared under cage and floor conditions in Bingöl province of Turkey. Japanese quails (1,000) were utilized for trials and measurements. Energy use efficiency, energy productivity, specific energy and net energy calculated under cage system was 0.11; 0.01 kg/MJ; 76.18 MJ/ kg and –12868.38 MJ/ (1,000 bird), respectively; and 0.09; 0.01 kg/MJ; 89.79 MJ/ kg and –13488.06 MJ/ (1,000 bird), respectively, under floor conditions. The total direct energy input was 17.11 and 16.61%, and indirect 82.29 and 83.39% under cage and floor conditions, respectively. The total renewable energy input was 79.65 and 83.33%, non-renewable as 20.35 and 16.67% under cage and floor conditions, respectively.Hence, the Japanese quail production under cage and floor conditions is not a viable activity in terms of energy usage. Modern and well established scientific practices should be used to obtain more energy efficiency and maximum economic benefits without overstressing the energy consumption. Further, using solar energy to warm up poultry house may be useful in increasing the energy usage ratio. Since, feed had the highest rate of total energy input, it may be reduced by keeping the chicks stress-free.